Plastic ingestion by Atlantic horse mackerel (Trachurus trachurus) from central Mediterranean Sea: A potential cause for endocrine disruption. (1st September 2021) - Chenet, Tatiana; Mancia, Annalaura; Bono, Gioacchino; Falsone, Fabio; Scannella, Danilo; Vaccaro, Carmela; Baldi, Andrea; Catani, Martina; Cavazzini, Alberto; Pasti, Luisa
Abstract: Plastics in the oceans can break up into smaller size and shape resembling prey or particles selected for ingestion by marine organisms. Plastic polymers may contain chemical additives and contaminants, including known endocrine disruptors that may be harmful for the marine organisms, in turn posing potential risks to marine ecosystems, biodiversity and food availability. This study assesses the presence of plastics in the contents of the gastrointestinal tract (GIT) of a commercial fish species, the Atlantic horse mackerel, Trachurus trachurus, sampled from two different fishing areas of central Mediterranean Sea. Adverse effect of plastics occurrence on T. Trachurus health were also assessed quantifying the liver expression of vitellogenin (VTG), a biomarker for endocrine disruption. A total of 92 specimens were collected and morphometric indices were analysed. A subgroup was examined for microplastics (MP < 1 mm) and macroplastics (MaP >1 cm) accumulation in the GIT and for VTG expression. Results indicated that specimens from the two locations are different in size and maturity but the ingestion of plastic is widespread, with microplastics (fragments and filaments) abundantly present in nearly all samples while macroplastics were found in the larger specimens, collected in one of the two locations. Spectroscopic analysis revealed that the most abundant polymers in MP fragments were polystyrene, polyethylene and polypropylene, whereas MP filaments were identified mainly as nylon 6, acrylic and polyester. MaP were composed mainly of weathered polyethylene or polypropylene. The expression of VTG was observed in the liver of 60% of all male specimens from both locations. The results of this study represent a first evidence that the ingestion of plastic pollution may alter endocrine system function in adult fish T. Trachurus and warrants further research. Graphical abstract: Image 1 Highlights: Presence of micro- and macroplastics in Atlantic horse mackerel evaluated. Specimen collected in two geographical locations of central Mediterranean Sea. Micro- and macroplastics identified by micro-Raman and IR spectroscopy. Morphometric data analysed in correlation with location and plastic ingestion. Vitellogenin expression observed in males possibly correlated to plastic ingestion. Abstract : Micro- and macroplastics affect morphology, growth and reproduction in the Atlantic horse mackerel of the central Mediterranean Sea.